Anthropometric measures of certain movements of men used while projecting machines and equipments - Batogowska, Anna (Anthropological Review, 1974)
The author gives descriptions of anthropometric examinations of certain functional characteristics of men and instruments used in this test. The measurements have been made on 860 individuals (406 ♂ and 454 ♀) which were specially chosen for this test. The following was tested: the movement of the inclination, straightening and the rotation of the head, the movements of the palms and feet. The results of thes are presented in the tables 1 - 4.